Assessment of Adaptive Capacity to Drought of Rainfed Rice Farmers in Maha Sarakham, Northeastern Thailand - Bridhikitti, Arika (วารสารแก่นเกษตร, 2019)
There is high confidence that Southeast Asia is seriously affected by climate changes, and poverty of farmers in this region is a major concern. This study aims to assess adaptive capacity to drought of rainfed rice farmers in the northeastern part of Thailand. The assessment was conducted through secondary data collection, field survey and interviews in four sub-districts across Kantarawichai District, Maha Sarakham, Thailand during the 2015−16 drought event. The results show the farmers’ background economic status and rice cropping practices. Long term rainfall record illustrated significant changes in rainfall magnitude and variability, trends and characteristics of the drought. The degree of adaptive capacity reveals that at the preparation and response phases, the farmers could be able to cope with the drought to some extents because of their high responsiveness to drought, high modularity, greatly addressing morality in decision making, and acknowledging social equity. After the drought, poor rice market system could significantly hamper the bounce-back ability of the farmers. Several adaptive options are suggested to build better adaptive capacity on future unprecedented drought.